1878 Iowa Acts 108, Military Code of Iowa, chap. 125, § 1 - (:unkn) unknown (General Publisher, 1878)
Included all able-bodied male citizens between the ages of eighteen and forty-five years as party of the militia
--
Keywords: ARMED FORCES